Penerapan Metode Hypnoteaching Dalam Upaya Meningkatkan Kecerdasan Otak Peserta Didik - Juliana Wahid; Ratih Juni Astuti (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
In the learning process, the methods used in the classroom by teachers is not the same between one another teacher. sometimes, a lot of teachers who generally just do learning methods have still minimal preparation, where teachers mostly just entered the classroom, explaining the material, then assign tasks, just about it without knowing the sense that raged within the student. In this case to resolve the issue there is a relatively new method and is still rarely known by educators, the method with hypnoteachingyang in which to discuss about how to become an active and creative teacher provides instruction through the subconscious of a student, sehgga authors were interested to examine more the associated application that is still minimal by teachers in the school, therefore, the authors conducted a study to take the title "Application Of Hypnoteaching Method in Efforts to Improve Brain Intelligence Of Students (Detailed Analysus Of Mina Grade IV Students in Al-Azhar School 27 Cibinong)”.In preaparing this paper the author used descriptive analysis method that aims to describe the phenomenon in school. uthor of direct observation in the classroom to observe a method that teachers in elementary shools Islam Al-Azhar 27 Cibinong, conduct interviews in writing to the student to teacher in classroom teaching. Based on the research results and observed by the author hypnoteaching methods that teachers in SD Islam Al-Azhar 27 cibinong very good, because the teachers are doing the learning method in accordance with the principles of the method hypnoteaching. Keywords: hypnoteaching. intelligence, brain, learning, students.